2021
DOI: 10.1016/j.jaip.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Food Insecurity Among Households with Dietary Restrictions: A National Survey

Abstract: Background Food insecurity dramatically increased because of the COVID-19 pandemic; however, little is known about pandemic-related food insecurity in households with dietary restrictions. Objective To examine pre-pandemic rates of and pandemic-related change in food insecurity among households with and without dietary restrictions. Methods A cross-sectional, panel-based survey of 3200 U.S. women was conducted in April 2020. Pre-pandemic food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Two single‐center studies found an increase in food insecurity in pediatric patients living in the United States during the pandemic, increased from 10% to 30% and from 11% to 31% respectively 21,22 . Increased food insecurity during the pandemic has also been reported in other chronic diseases 23,24 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two single‐center studies found an increase in food insecurity in pediatric patients living in the United States during the pandemic, increased from 10% to 30% and from 11% to 31% respectively 21,22 . Increased food insecurity during the pandemic has also been reported in other chronic diseases 23,24 …”
Section: Discussionmentioning
confidence: 97%
“…21,22 Increased food insecurity during the pandemic has also been reported in other chronic diseases. 23,24 The etiologies for increased food security were multifactorial but seemed to be primarily financial. More food insecure subjects reported loss of employment, decreased household income, or difficulty obtaining food due to finances compared to food secure subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining food and groceries by supermarkets or food shops' delivery services was not common in the three countries (10%) (Lebanon, Tunisia, and Jordan) and was significantly the least reported among the Tunisians ( 17 ). All in all, it appears that households with dietary restrictions were more likely to experience both pre-pandemic and pandemic-related incident or worsening food insecurity than households without restrictions ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“… 27 Studies in various countries analyzed individuals’ perceived risk and anxiety of adhering to a gluten-free diet in the early months of COVID-19. 28 30 For individuals with gastrointestinal diseases, lack of access to personal products such as toilet paper during the early months of the pandemic likely caused increased psychological distress. 31 Studies conducted in Brazil and Australia during the pandemic did not indicate that individuals with celiac disease experienced decreased quality of life during the pandemic.…”
Section: Access To Gluten-free Food and Maintaining A Gluten-free Dietmentioning
confidence: 99%